Knowledge evaluation and disciplinary access: mutually supportive for learning. (3rd July 2022) - Ash, Andrea Malek; Hand, Brian
ABSTRACT: The centrality of knowledge construction to student learning is well-recognised in education. In this study, we explore what it means to go beyond knowledge construction to knowledge evaluation, and how knowledge evaluation combined with direct disciplinary access improves opportunities for meaningful learning. We first review literature to advance a theoretical understanding of a) the importance of student evaluation of knowledge and b) direct disciplinary access, and then review how both of these in tandem support students' learning with science content. We then use a single case study with a highly effective teacher to better understand the practical significance of these topics. Findings demonstrate how the teacher's approach supported students' opportunities to evaluate (rather than just construct) knowledge, which improved students' meaning-making around science concepts. Her approach also supported students' direct and unmediated access to science content, which has further implications for their scientific literacy and civic engagement. In describing the link between knowledge evaluation and direct disciplinary access in one teacher's classroom, we further articulate what it means for students to take a central role in the evaluation and use of science knowledge.